Active citizenship and disability : implementing the personalisation of support - Power, Andrew, 1979-; Lord, Janet E., 1966-; DeFranco, Allison S., 1983-; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
This book provides an international comparative study of the implementation of disability rights law and policy focused on the emerging principles of self-determination and personalisation. It explores how these principles have been enshrined in the United Nations Convention on the Rights of Persons with Disabilities and how different jurisdictions have implemented them to enable meaningful engagement and participation by persons with disabilities in society. The philosophy of 'active citizenship' underpinning the Convention - that all citizens should (be able to) actively participate in the community - provides the core focal point of this book, which grounds its analysis in exploring how this goal has been imagined and implemented across a range of countries. The case studies examine how different jurisdictions have reformed disability law and policy and reconfigured how support is administered and funded to ensure maximum choice and independence is accorded to people with disabilities.
pt. 1. Towards active citizenship for persons with disabilities. Supports to persons with disabilities in the context of international and regional disability law and policy ; Revitalising disability support at the domestic level -- pt. 2. Learning from comparative perspectives. Active citizenship and disability in the United States ; Active citizenship and disability in Canada (British Columbia and Ontario) ; Active citizenship and disability in the United Kingdom (England and Northern Ireland) ; Active citizenship and disability in Sweden ; Active citizenship and disability in France -- pt. 3. The development of reform in the disability support sector in Ireland. Tracing the origins of disability support in Ireland ; Towards active citizenship and disability in Ireland -- pt. 4. The journey ahead for active citizenship and independent living for persons with disabilities. Options and alternatives for a new support delivery framework which encourages independence.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: People with disabilities -- Legal status, laws, etc; Convention on the Rights of Persons with Disabilities and Optional Protocol -- (2007 March 30); Electronic books